Dinamika Pembaharuan Hukum Keluarga Islam: Studi Analisis Penerapan Hukum Perkawinan di Brunei Darussalam - Farizal Antony; Farid Anfasa; Mufliha Wijayati; Linda Firdawaty (Laskar Karya, 2024)
This study examines the dynamics of Islamic family law reform, focusing on marriage law in Brunei Darussalam as a living law continuously adapting to changing times. The research aims to analyze the development of marriage law in Brunei through a literature review integrating historical and normative approaches. Data were obtained from primary sources, such as the Syariah Court Evidence Order 2001 and the Islamic Family Law Order 2010, as well as relevant secondary literature. The findings reveal that family law reform in Brunei reflects efforts to balance Islamic Sharia principles with the needs of modern legal development, including regulations on the minimum marriage age, protection of women's rights, and polygamy governance. The conclusions emphasize the importance of harmonizing family law with international norms without neglecting Sharia principles. This study recommends strengthening regulations to enhance family protection, particularly for women and children, as part of the sustainable strategy for Islamic family law reform in Brunei Darussalam.